The N-terminus of fission yeast DNA polymerase alpha contains a basic pentapeptide that acts in vivo as a nuclear localization signal. - Bouvier, D (1995)
The N-terminal sequence of the catalytic subunit of fission yeast DNA polymerase alpha (pol alpha) contains two putative nuclear localization signals (NLS). To check the functionality of these signals in vivo, the N-terminal sequence was experimentally divided into three amino acid blocks, two of which contain a distinct presumptive NLS. Each block was deleted, either individually or in combination with one of the two others. The deleted gene products were expressed in fission yeast, and assayed by indirect immunofluorescence for their aptitude to localize to the cell nucleus. Block II, which contains the putative NLS pentapeptide 97RKRKK, was both necessary and sufficient to promote nuclear import of pol alpha, as well as of a pyruvate kinase fusion protein. Precise excision of the NLS pentapeptide from block II inhibited the nuclear import of pol alpha, thus confirming the role of this sequence as the functional NLS of the fission yeast enzyme.